Overexpression of NTPCS1 Enhances Zn Tolerance in Tobacco - Chanjuan Wu; Jie Zhang (Plants)
Phytochelatins (PCs) are well-characterized for their role in detoxifying non-essential metals like cadmium (Cd), but their role in zinc (Zn) homeostasis remains underexplored. In this study, we investigated the role of the Nicotiana tabacum phytochelatin synthase 1 (NtPCS1) in counteracting Zn toxicity in plants. qRT-PCR data showed that the transcript level of the NtPCS1 gene was upregulated by ZnSO4, leading to increased PC production in the wild-type tobacco plants. Functional complementation assays in Arabidopsis thaliana revealed that overexpression of NtPCS1 rescued the Zn hypersensitivity of the Atpcs1 mutant, with the N-terminal region being indispensable for Zn tolerance. In addition, transgenic tobacco plants overexpressing NtPCS1 (PCS1 lines) exhibited superior root elongation under ZnSO4 stress compared to the wild-type plants, particularly when supplemented with glutathione (GSH). The observed phenotypic advantage is attributed to NtPCS1-mediated overproduction of PCs, which facilitated Zn chelation and enabled cellular detoxification. These findings highlight the important role of NtPCS1 in Zn tolerance via GSH-linked PCs synthesis, offering insights into PCS-mediated Zn detoxification and a genetic strategy for developing Zn-resistant plants.